Pengaruh Kecerdasan Emosional terhadap Prestasi Belajar Siswa Madrasah Ibtidaiyah - Sari, Ira; Azura, Wan; Utami, Sheila (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2025)
Student learning achievement is one of the indicators of the success of the educational process. However, achievement is not only determined by intellectual ability but also by emotional intelligence, which plays a role in managing emotions, building social relationships, and motivating oneself to learn. This study aims to analyze the influence of emotional intelligence on the learning achievement of elementary school students. The research method used is quantitative with a correlational approach. Data collection techniques were conducted through questionnaires to measure emotional intelligence and documentation of grades as indicators of learning achievement. The study population consists of all fifth-grade students totaling 22 students, and the sample was determined using purposive sampling. The research results show that the emotional intelligence of students is in the "agree" category, which means it is quite good, with an average score of 3.915. Meanwhile, the learning achievement of students is also in the "agree" category with an average score of 3.885. The results of the simple linear regression test show that there is a significant influence of emotional intelligence on student learning achievement, with a significance value less than 0.05. The implication of this research is the importance of strengthening character education and emotional intelligence training in the learning process at the primary level to optimally support learning achievement